High Drop-off Along the HIV Care Continuum and ART Interruption Among Female Sex Workers in the Dominican Republic. (1st June 2015) - Zulliger, Rose; Barrington, Clare; Donastorg, Yeycy; Perez, Martha; Kerrigan, Deanna
Abstract : Background: Engagement in HIV care offers clear individual and societal benefits, but little evidence exists on the care experiences of key populations. Methods: A cross-sectional survey was conducted with 268 female sex workers (FSWs) living with HIV in Santo Domingo, Dominican Republic, to describe the HIV care continuum and to determine factors associated with antiretroviral therapy (ART) interruption. Results: FSWs disengaged throughout the care continuum with the highest drop-off after ART initiation. Most participants were linked to care (92%), retained in care (85%), and initiated onto ART (78%), but ART discontinuation and irregular adherence were frequent. Only 48% of participants had an undetectable HIV viral load. Overall, 36% of participants ever initiated onto ART reported lifetime experience with ART interruption. The odds of ART interruption were 3.24 times higher among women who experienced FSW-related discrimination [95% confidence interval (CI): 1.28 to 8.20], 2.41 times higher among women who used any drug (95% CI: 1.09 to 5.34), and 2.35 times higher among women who worked in an FSW establishment (95% CI: 1.20 to 4.60). Internalized stigma related to FSW was associated with higher odds of interruption (adjusted odds ratio: 1.09; 95% CI: 1.02 to 1.16), and positive perceptions of HIV providers were protective (adjusted odds ratio: 0.91; 95% CI: 0.85 to 0.98). Conclusions: FSWs living with HIV confront multiple barriers throughout the HIV care continuum, many of which are related to the social context and stigmatization of sex work. Given the clear importance of maximizing the potential benefits of engagement in HIV care, there is an urgent need for interventions to support FSWs throughout the HIV care continuum.